Brain Drain, Educational Quality and Immigration Policy: Impact on Productive Human Capital in Source and Host Countries, with Canada as a Case Study - Maurice Schiff (Institute for the Study of Labor (IZA), 2014)
With the 1967 reform, Canada's immigration policy changed from a country-preference system to a points system. The latter provides points according to applicants' education level but abstracts from the quality of their education. This paper considers the points system, the country-preference system, as well as a system that includes both educational quantity and quality and is termed the "𝑞2 points system." It focuses on the policies' impact on immigrants' average productive human capital the product of educational quality and quantity or skill level, 𝑆𝑥 (for policy 𝑥). It shows, among others, that i) 𝑆𝑥 is greater under the 𝑞2 system than under the points system (𝑆𝑞 > 𝑆ℎ); ii) a switch from a points system to a 𝑞2 system results in a human capital gain or net brain gain for Country 1 (the high-education quality country) and a loss or net brain drain for Country 2; iii) 𝑆𝑥 is greater under the country-preference system than under the points system (𝑆𝑝 > 𝑆ℎ); iv) whether 𝑆𝑥 is greater under the 𝑞2 or the country-preference system is ambiguous, with 𝑆𝑞 >(<) 𝑆𝑝 if the quality of education in Country 1 relative to Country 2 is higher (lower) than the degree of preference for migrants from Country 1 relative to Country 2; and v) an increase in education quality in the high- (low-) quality source country has a positive (ambiguous) impact on 𝑆𝑥 under all three policies and the impact is larger under the 𝑞2 than under the points system.
Keywords: F22; I20; 330; points system; country-preference system; education quantity-quality system; Canadian immigration policy; human capital impact